Distribution of haplotypes from a chromosome 21 region distinguishes multiple prehistoric human migrations - Jin, Li (The National Academy of Sciences, 1999)
Despite mounting genetic evidence implicating a recent origin of modern humans, the elucidation of early migratory gene-flow episodes remains incomplete. Geographic distribution of haplotypes may show traces of ancestral migrations. However, such evolutionary signatures can be erased easily by recombination and mutational perturbations. A 565-bp chromosome 21 region near the MX1 gene, which contains nine sites frequently polymorphic in human populations, has been found. It is unaffected by recombination and recurrent mutation and thus reflects only migratory history, genetic drift, and possibly selection. Geographic distribution of contemporary haplotypes implies distinctive prehistoric human migrations: one to Oceania, one to Asia and subsequently to America, and a third one predominantly to Europe. The findings with chromosome 21 are confirmed by independent evidence from a Y chromosome phylogeny. Loci of this type will help to decipher the evolutionary history of modern humans.